Synthesis of Trifluoromethyl Ketone Containing Amino Acid Building Blocks for the Preparation of Peptide-Based Histone Deacetylase (HDAC) Inhibitors - Moreno-Yruela, Carlos; Olsen, Christian A. (Synthesis, 2018)
Trifluoromethyl ketones (TFMKs) are electrophilic moieties which hydrate readily in aqueous media to give geminal diols. This ability has been exploited for the development of histone deacetylase (HDAC) inhibitors, because HDAC enzymes contain a Zn2+ ion which may be chelated by this functionality. Interestingly, TFMKs are exceptional Zn2+-binding groups for targeting the intriguing class IIa HDAC isozymes, involved in transcription factor recruitment and gene regulation. Here, we have developed a scalable and inexpensive synthetic procedure for preparation of the enantiomerically pure TFMK-containing amino acid building block (S)-2-amino-9,9,9-trifluoro-8-oxononanoic acid (Atona). In addition, we propose a protecting group strategy applicable to automated solid-phase peptide synthesis and demonstrate the ability of Atona-containing peptides to inhibit the enzymatic activity of class IIa HDACs with nanomolar potency. We envision that this synthesis will motivate the further development of peptide-based probes for the study of class IIa HDACs.
Keywords: trifluoromethyl ketones; histone deacetylase; histone deacetylase inhibitors; epigenetic; amino acids; peptides; protecting groups